306 Application of genomic selection for enhancing health, welfare, efficiency and production traits in turkeys. (7th December 2018) - Malchiodi, F; Wood, B; Barbut, S; Harlander, A; Baes, C
Abstract: The implementation of single-step genomic BLUP (ssGBLUP) to selection programs can considerably increase the accuracy of breeding values, and therefore the ability to estimate the genetic merit, of livestock. In particular, traits with low heritability, such as livability and other health and welfare traits, are amenable to genomic selection. Effective application of ssGBLUP requires genomic information, population-based pedigree data, and high-quality phenotypes. The aim of this research is to apply ssGBLUP to commercial turkey lines (15, 000 turkeys genotyped at 65K). This population will be used to assess the increase in accuracy of selection using genomic information, and to monitor inbreeding within the different lines. In addition to the high-quality phenotypes available related to fertility, growth, production, and carcass composition, auxiliary health and behaviour phenotypes related to livability will be investigated. Furthermore, novel meat quality (e.g. water holding capacity, pH, sheer force and colour) and total carcass composition phenotypes will also be identified and collected.With improved methodology, more detailed phenotypic information, and comprehensive data collection and integration, more accurate selection of parent stock will be possible.